The guise of another - Eskens, Allen, 1963- (Seventh Street Books, an imprint of Prometheus Books, 2015)
After being subpoenaed by a grand jury under suspicion of corruption, Minnesota detective Alexander Rupert attempts to salvage his career and reputation investigating the false identity of recent car accident victim.